PENANGANAN LAPORAN DAN PENGADUAN KORBAN KEJAHATAN OLEH KEPOLISIAN SEKTOR TAMPAN KEPOLISIAN RESOR KOTA PEKANBARU - Rendriana, Cut Tita; Lestari, Rika; R, Mukhlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The problem of crime or criminal offenses currently is increasing, various forms of crime and modus operandi can occur at any time and at any time along with the development and growth of the population, as well as in the District Tampan of Pekanbaru. Therefore, the role and effective coordination between the Police and the community is very important in providing a sense of security to witnesses and victims of criminal acts. The purpose of this thesis are: First, Handling Reports and Complaints Victims of Crime by the Police Sector of Tampan, Second, Obstacles encountered in the Reports and Complaints Handling Victims of Crime by Tampan Police Sector, Third, efforts made in Overcoming Barriers to Treatment Reports and Complaints Victims crime by the Police Sector of Tampan. This type of research can be classified into types of juridical sociological research. This research was conducted in the Police Sector Handsome, while the population and the sample is a whole party relating to the issues examined in this study, the data sources used, the primary data, secondary data, and the data tertiary. Data collection techniques in this study with interviews, observation, and literature study. Analysis of the data used is qualitative data and techniques by means of deductive inference. From the research, there are three main issues that can be inferred. First, Handling Reports and Complaints Victims of Crime by the Police Sector of Tampan District of Pekanbaru City Police have not conducted pursuant to Act No. 2 of 2002 on the Police and the Police Regulation No. 2 of 2012 on Public Complaints Handling Procedures in Environmental Police of the Republic of Indonesia. Second, obstacles encountered in the handling of reports and complaints of victims of crime by police Tampan sector is lack of awareness in giving testimony / witness in the police force, presence of motivational factors and risk factors, lack of police personnel, lack of facilities and infrastructure. Third, efforts are being made to overcome the obstacles in the handling of reports and complaints of victims of crime by police Tampan sector ie, preventive approaches and infrastructure approach, Suggestions Author, First, a need for special supervision over the handling of the complaint in the police report and handsome sector due to still have a few persons who are not serious in handling a case. Secondly, provision should be made legislation governing cross-sectoral coordination between institutions or law enforcement agencies relating to the handling of reports and complaints of victims of crime. Third, there needs to be a serious commitment, fast, and decisively from the Government to open up access to the widest public and relevant agencies handling complaints in the police reports and sector including the provision of facilities and infrastructuret.